The use of soil palynomorphs in forensics - A.A. Abdulrahaman; A.A. Al Sahli; J.U. Okoli (Journal of Applied Sciences and Environmental Management, 2018)
The aim was to establish the forensic value of using palynomorphs in soil samples to link people or objects to crime scenes in order to establish or strengthen an association. This was done by determining the degree to which pollen assemblages of surface soil samples differ within the same area. Samples within the same localized area (the control site) showed a high degree of similarity, suggesting that pollen assemblages of surface soil samples from within a localized area are homogeneous. Standard methods were used for the collection and analysis of soil samples such as deflocculation, acetolysis for removal of cellulose and organic matter and silicate removal method to achieve better visualization and identification of pollen types. The results indicated that the cast of footprints and palm prints provided evidence of a two way transfer of materials between the palms and feet and the soil of the grassy area. Pollen analysis of the soil that had adhered to the palms and feet showed that the perpetrator of the imprint had been standing in that grassy area. The analysis of the interface between the body parts (palms and feet) and soil is therefore a potentially lucrative source of information for forensic reconstruction. This analysis shows that pollen can be used to associate perpetrators to crime scenes and should be seen as a useful tool in the analysis of hitherto unrecognized forensic materials in forensic palynology.